Evaluation of skin-mounted sensor for head impact measurement. (July 2019) - Tiernan, Stephen; Byrne, Gary; O'Sullivan, David Michael
The requirement to measure the number and severity of head impacts in sports has led to the development of many wearable sensors. The objective of this study was to determine the reliability and accuracy of a wearable head impact sensor: xPatch, X2Biosystems, Inc. The skin-mounted sensor, xPatch, was fixed onto a Hybrid III headform and dropped using an impact test rig. A total of 400 impacts were performed, ranging from 20g to 200g linear acceleration, and impact velocities of 1.2 - 3.9 m/s. During each impact, the peak linear acceleration, angular velocity and angular acceleration were recorded and compared to the reference calibrated data. Impacts were also recorded using a high-speed video camera. The results show that the linear acceleration recorded by the xPatch during frontal and side impacts had errors of up to 24% when compared to the referenced data. The angular velocity and angular acceleration had substantially larger errors of up to 47.5% and 57%, respectively. The location of the impact had a significant effect on the results: if the impact was to the side of the head, the device on that side may have an error of up to 71%, thus highlighting the importance of device location. All impacts were recorded using two separate xPatches and, in certain cases, the difference in angular velocity between the devices was 43%. In conclusion, the xPatch can be useful for identifying impacts and recording linear accelerations during front and side impacts, but the rotational velocity and acceleration data need to be interpreted with caution.